100=2(3+6n)-2

Simple and best practice solution for 100=2(3+6n)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 100=2(3+6n)-2 equation:



100=2(3+6n)-2
We move all terms to the left:
100-(2(3+6n)-2)=0
We add all the numbers together, and all the variables
-(2(6n+3)-2)+100=0
We calculate terms in parentheses: -(2(6n+3)-2), so:
2(6n+3)-2
We multiply parentheses
12n+6-2
We add all the numbers together, and all the variables
12n+4
Back to the equation:
-(12n+4)
We get rid of parentheses
-12n-4+100=0
We add all the numbers together, and all the variables
-12n+96=0
We move all terms containing n to the left, all other terms to the right
-12n=-96
n=-96/-12
n=+8

See similar equations:

| -10y^2+33y-26=0 | | 17/5x-4x=-2=-2x+21/20 | | 3x+42-x=10 | | 2/3x+6=1/2x=1/4 | | 102+19m=330 | | 31n-102=425 | | 38=-8+5(x+4) | | X²(x-9)(2x+1)=0 | | 5p+13/2=14 | | 1/12y-2=-10 | | -(5r+4)=-2(2+5r)-5 | | 1/12y+3=-15 | | 160=120/a(144) | | y/8+8=-13 | | 3x-7x=-4(x-6)-8(7-x) | | 6x²+x-15=0 | | (x+4)²-8x=0 | | -3(4p-2)=21-7p | | -4(-3+6x)=-15+3x | | 6=-3x-33 | | -2(8n-3)=-90 | | 5x-24=3x+76 | | 128=-8(m-2)-6m | | g=9.81*50/0.5^2 | | 3x+6=-2x+5 | | 8x-(4x-8)=2+ | | 9(t-2)=5(10t-5) | | 2x³+11x²+17x+6=0 | | 6y/2y-5/2y=7/9 | | (x^2/3)-(50x^2)-1000x=0 | | x+5/11=1/22 | | 6y/2y-5y/2y=7/9 |

Equations solver categories